2021
DOI: 10.1001/jamanetworkopen.2020.36725
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Interprofessional Collaborative Practices and Outcomes in Adults With Diabetes and Hypertension in Primary Care

Abstract: IMPORTANCE Interprofessional collaborative practice (ICP), the collaboration of health workers from different professional backgrounds with patients, families, caregivers, and communities, is central to optimal primary care. However, limited evidence exists regarding its association with patient outcomes. OBJECTIVE To examine the association of ICP with hemoglobin A 1C (HbA 1c), systolic blood pressure (SBP), and diastolic blood pressure (DBP) levels among adults receiving primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 69 publications
4
46
0
6
Order By: Relevance
“…Of particular note is that the percentage of patients at blood pressure goal improved remarkably over the course of the study from 50.8% to 84.6%. In congruence with previously published research [ 24 , 32 , 33 , 40 , 41 ], our study findings showed a clinically significant reduction both in SBP (9.0 mmHg) and DBP (4.9 mmHg). As reported by the European Society of Cardiology, meta-analyses of RCTs have shown that a 10 mmHg reduction in SBP or a 5 mmHg reduction in DBP has a strong clinical impact on all major CV events, all-cause mortality, stroke, coronary events, and heart failure, hence rendering our study findings highly relevant [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Of particular note is that the percentage of patients at blood pressure goal improved remarkably over the course of the study from 50.8% to 84.6%. In congruence with previously published research [ 24 , 32 , 33 , 40 , 41 ], our study findings showed a clinically significant reduction both in SBP (9.0 mmHg) and DBP (4.9 mmHg). As reported by the European Society of Cardiology, meta-analyses of RCTs have shown that a 10 mmHg reduction in SBP or a 5 mmHg reduction in DBP has a strong clinical impact on all major CV events, all-cause mortality, stroke, coronary events, and heart failure, hence rendering our study findings highly relevant [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…The obtained results indicate that provision of the pharmaceutical care practice in the primary healthcare setting in Croatia improves patients’ clinical parameters such as blood pressure, TC, LDL-C, and HbA1c, and reduces healthcare utilisation. The results of this study are consistent with previous research, indicating improvements in clinical outcomes and avoidance of healthcare service utilisation in the CMM group [ 9 ] and interprofessional collaborative practices in general [ 40 ]. Furthermore, this is the first quasi-experimental study with the inclusion of a non-random control group that used the methodology of Cipolle et al [ 36 ] in the provision of pharmaceutical care to older CV patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Tais dificuldades perpassam, em boa parte, pelos desafios impostos por concepções de masculinidade que modulam o comportamento desse grupo social (18) . No entanto, é necessário que os enfermeiros persistam na realização de intervenções de apoio ao autocuidado de homens com diabetes, especialmente em perspectiva interprofissional e colaborativa, pois, quando participam de intervenções dessa natureza, são identificados benefícios, como redução de fatores de risco cardiometabólicos (19) .…”
Section: Resultsunclassified
“…In this way, studies show the importance of strong implementation strategies involving partnerships between all professionals of the Basic Health Units, as it could be possible to have a broad portrait of the community and the consequent development and encouragement of the use of specific techniques and processes to promote quality health (23) . The expansion of strategies for other sexual and gender minorities (lesbians, gays, bisexuals, and transsexuals) can be encouraged since this population has less adherence to preventive exams for fear of stigma and discrimination.…”
Section: Catalyzing Change […] Regarding the Prevention Of Cervical And Breast Cancer From Time To Time I'll Do An Educational Practice [mentioning
confidence: 99%